The Relationship Between Age And Gender And The Time To Achieve Euthyroid Condition In Graves' Disease Patients Who Receive Antithyroid Drug Therapy - Nanang Miftah; Ladika Avicena Dzikaf Masyahiro Mohtar; Hendra Wana Nur'Amin; Fauzia Noor Liani; Alfi Yasmina (Green Publisher Indonesia, 2025)
Graves' disease is an autoimmune disease that most common cause of hyperthyroidism which is characterized by diffuse thyroid disease, thyrotoxicosis, and can be accompanied by orbitopathy and dermopathy. Age and gender are factors that are thought to influence the time it takes for GD patients to reach a euthyroid state who receive antithyroid drug therapy. The aim of this study was to determine the relationship between age and gender on the time to achieve euthyroidism in GD patients who received anti- thyroid drug therapy. This analytical observational study is a cohort study conducted using the Borneo Wetland Study on Thyroid 2 (BEST-T 2) Endocrine Polyclinic, Ulin Hospital Banjarmasin database. Data on 68 GD patients were taken using the total sampling method. Data were analyzed using the Cox Regression test with SPSS version 26 with a confidence level of 95%. Survival data will be displayed using the Kaplan Meier curve. This study showed that there was no relationship with age (p=0.064), but showed there was a relationship with gender (p=0.044) on the time to achieve euthyroidism in Graves' disease patients.